Is Shari'ah corporate governance framework necessary for Islamic capital market? - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)

(untitled)
Islamic finance industry has rapidly penetrating into both Muslim and non-Muslim countries since a last few decades. Islamic finance industry comprises of the Islamic banking, Takaful and Islamic capital market. These three main industries are interrelated and dependent on each other in order to ensure that the whole Islamic financial system is in compliance with the Islamic principles. Among these three streams of the service industry, the Islamic capital market plays an important role to support the other two industries. Among the countries which support Islamic finance industry, Malaysia is trying to be the hub of Islamic finance and it has issued the Shari’ah Governance Framework (SGF) specifically for Islamic banking sector under the supervision of the Central Bank of Malaysia. It mainly focuses on Islamic banking and Takaful, not Islamic capital market. This capital market is operating under Security Commission. Hence, the objective of this research is to investigate on whether there is a need for a comprehensive Shari’ah governance framework focused on Islamic capital market. This research is based on the library research by reviewing the selected literature. The findings suggest that in the case of Islamic Shari’ah corporate governance, its source of ruling is originated and based on the Islamic teaching. Islamic accountability should be always in the heart of corporate players and their decisions should be focused not only on the shareholders but also for the other stakeholders within the framework of Shari’ah. This paper will be the interest of the investors, market players and regulators.